Serum Vitamin D Level in Chronic Obstructive Pulmonary Disease and its Relation with Severity - Ubaid Ullah Sami, Saeed Ur Rehman, Adnan Ghafoor, Zayed Naser, Saleh Ahmad, Hafeez Ud Din, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The COPD is a serious epidemic-level public health issue. Patients with COPD have been found to have low vitamin D serum levels in a number of studies. Aim: The goal of the study was to determine whether there was a relationship between vitamin D serum levels and the severity of COPD by comparing the levels in COPD patients at stages II, III, and IV to those in the control group. Study Design: A Cross-sectional study Place and Duration: In the Pulmonology department of Lady Reading Hospital, Peshawar and District Headquarter Hospital, Timergara Dir-Lower KPK during the period from January 2022 to June 2022. Methods: The study included 140 participants in total, including 70 COPD patients and 70 controls for comparison. Patients were included from the outpatient department and medical wards. According to GOLD guidelines, advanced COPD staging II, III, and IV were done. In SPSS 21.0, inferential and descriptive statistics were accomplished. Results: COPD was found in 34.3%, 37.1%, and 28.6% of people in stages II, III, and IV, respectively. There was a statistically significant relationship between lower vitamin D levels and advanced COPD patients, with the mean vitamin D serum concentration in COPD patients being 16.01 ng/ml and the vitamin D mean concentration in healthy controls being 35.98 ng/ml. (p<0.0001). The severity of COPD was supposed to be inversely related with vitamin D serum levels. Conclusions: The vitamin D serum levels were found lesser in patients with advanced COPD (stages II, III, and IV) than in the general population correlated with GOLD staging. Keywords: Global initiative for chronic obstructive lung diseases; Chronic obstructive pulmonary disease and Vitamin D levels